Real-Time Women Security Assistance System with Enhanced Features - C., Thippeswamy; G., Sireena Bhanu; D., Rahul; G., Sindhu Priya; B., Prabhakar (Journal of ISMAC, 2026)
This paper provides improved security for women and children by implementing GPS and GSM modules into a system similar to a smartwatch-based device. The system was designed to provide real-time tracking, emergency alerts, and recorded evidence collection to ensure immediate assistance in emergency situations. When a wearable device’s push button is repeatedly pressed, victims can send their location information to registered contacts and the closest police station, allowing for prompt action. Additionally, the device has audio and video recording features that will be activated automatically, preserving important proof for further investigation. Unlike basic safety applications that depend on internet connectivity, this work uses GSM-based SMS alerts, making it extremely effective even in low-network areas. The emergency function is activated only when the button is touched multiple times, which triggers the alert and sends it only to emergency contacts to prevent false alarms. An emergency contact can remotely access the user’s location by sending a specific SMS message, providing an additional layer of security. By combining current technology with user-based safety measures, this device encourages women and children to take control and provides response controls, real-time tracking, and automatic operation, resulting in a dependable and efficient personal security solution.